Psychometric evaluation of the Positivum beliefs and perceptions scales to inform occupational rehabilitation following injury - Dianne M. Sheppard; Ljoudmila Busija; Gabrielle May; Dorothy Frost (PLoS ONE, 2025)
Negative beliefs and perceptions about one’s health and work participation can act as barriers to rehabilitation and returning to work following an injury, thus increasing the risk of long-term work disability. To prevent poor work and health outcomes it is necessary to be able to effectively measure such constructs. The aim of the present study was to perform a psychometric evaluation of the PositivumTM: Beliefs and Perceptions scales used with individuals with a musculoskeletal injury or condition receiving occupational rehabilitation (OR) services through a workers’ compensation or motor vehicle accident insurance scheme. Exploratory factor analysis, item response theory-based analyses, internal consistency analyses, and confirmatory factor analysis were conducted on data collected from January 2020 to April 2024 from a sample of 3,352 musculoskeletal injured individuals receiving OR services through their compensation scheme. The results of the current study demonstrated the psychometric robustness of a revised 12 item Positivum: Beliefs and Perceptions scale (PBPS), with two clear multi-item factors: Employer Perceptions and Health-related Work Beliefs as well as two single-item measures (expectations about, and perceived enjoyment of, working). Identifying those with negative beliefs and perceptions about working following an injury and at risk of prolonged work disability is the first critical step toward preventing prolonged work disability.